Factors That Affect Saudi Population Preferences Toward Their Dentist - Alsaeed S (Dove Medical Press, 2021)
Suliman Alsaeed,1– 3 Norah Alghurairi,4 Lamia Almutairi,4 Afrah Alossimi,4 Afnan Bin Fadhl,4 Sadeem Abahussain4 1Preventive Dental Sciences Department, College of Dentistry, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 2King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 3Ministry of the National Guard - Health Affairs, Riyadh, Saudi Arabia; 4College of Dentistry, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi ArabiaCorrespondence: Suliman AlsaeedCollege of Dentistry, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi ArabiaEmail saeedsu@ksau-hs.edu.sa; suliman.as@hotmail.comObjective: To explore the preference of Saudi population when selecting their dentist.Design: Cross-sectional observational study.Methods: An online questionnaire was distributed in Arabic language. The inclusion criteria were Saudi participants, aged 18 years or above. The questionnaire was divided into four sections that included participants’ demographic data, preferred criteria on dentists and dental office design, and table for the importance of each of the factors studied.Results: A sample size of 5317 participants completed the questionnaire with a mean age of 30.5 ± 11.6 years old, 57% were females. Most of the participants had no preference on their dentist’s nationality (63%) or gender (44%). There was a preference for dentists who are consultants (38%), well known (83%), and has an explanatory-style consultation (78%). Participants preferred scrub and lab coat attires for their male (41%) and female (38%) dentists. Less than half of the participants (44.8%) preferred the dentist to have a social media account. Of all social media platforms, Twitter was the most preferred one (37%). White clinic color was more preferable than other colors (56%). Of all the factors studied, dentist’s reputation, clinical rank and cost of treatment were considered very important for most of the participants when selecting their dentist.Conclusion: Overall, Saudi participants have specific preferences on their dentists and dental office design. Dentists might consider these factors to improve their dental practice and their patients’ experience.Keywords: patients’ preferences, dentistry, private practice, Saudi population, marketing